Evaluation Study of Sports and Health Physical Education Learning Programs at Inclusion Elementary Schools in Purworejo Regency - Widodo, Endro; Nopemberi, Soni (International Forum of Researchers and Lecturers, 2025)
This research primary objective is to describe the evaluation of Physical Education learning programs in inclusive elementary schools located in Purworejo Regency. The focus is on: (1) analyzing the preparation process for Physical Education learning in inclusive elementary schools, (2) analyzing the implementation process for Physical Education (PE) learning activities in inclusive elementary schools, and (3) analyzing the assessment methods for Physical Education learning in inclusive elementary schools. This research employed an evaluation research method with a Concurrent Embedded (unbalanced mixed) design. The data were analyzed by using the Countenance Stake Model. This model emphasizes two types of operations: description and judgment, distinguished three phases in the evaluation of Physical Education learning in inclusive elementary schools: (1) the antecedent stage, (2) the transaction stage, and (3) the outcomes stage. The research subjects were school supervisors, principals, Physical Education teachers, and parents of students. The data collection techniques used questionnaires, interviews, observation, and documentation. The data were analyzed by using descriptive quantitative and descriptive qualitative analysis techniques. The research findings indicate: (1) the preliminary stage (antecedent), the description of PE learning, is in the good category, because the learning objectives have been adjusted to the conditions of the students, teachers have the qualifications to be able to develop semester programs, syllabi, and lesson plans, the condition of supporting infrastructure, teachers' comprehension on learning strategies and mastery of PE learning materials; (2) the process stage (transaction), the description of PE learning, is in the good category because the implementation of PE learning is in accordance with the curriculum, using integrative thematic learning with a scientific approach and the implementation of authentic assessment; (3) the results stage (outcomes), the measurement of the results of assessments conducted by teachers covering aspects of attitude, knowledge, and skills in PE learning, is in the good category but has not been carried out comprehensively to assess input, process, and output/results.